THERMAL IDENTIFICATION BASED ON BUILDING ENVELOPE, SHAPE & ORIENTATION USING SEFAIRA SIMULATION METHOD. (CASE STUDY OF BUILDING B, ARCHITECTURE DEPARTMENT, UNIVERSITY OF LAMPUNG) - Ifadianto, Nugroho; Kurniawan, Panji; Nugroho, Agung Cahyo; Siregar, Amril Ma'ruf (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
The building envelope, which serves as the boundary layer between the interior and exterior, plays a crucial role in regulating heat exchange. The shape of the building also impacts heat distribution and airflow within and around the structure. The orientation of the building, particularly in relation to the sun, determines how much solar radiation it receives, directly affecting the building's thermal load.Using Sefaira, a building performance simulation software, researchers can visualize and optimize these thermal aspects. This simulation allows them to experiment with various scenarios related to the building envelope, shape, and orientation to achieve ideal thermal conditions, which are not only comfortable for occupants but also energy-efficient.The findings of this research are expected to provide new insights into sustainable architectural design, especially in tropical regions like Lampung. By understanding and applying the correct thermal principles, buildings can be designed to minimize energy usage for cooling or heating, supporting efforts to reduce the impacts of climate change